2021
DOI: 10.3389/fcimb.2021.594808
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Molecular Method for Simultaneous Identification of Vibrio parahaemolyticus 57 K-Serogroups Using Probe Melting Curve Analysis

Abstract: The serotyping of Vibrio parahaemolyticus, which is crucial to the surveillance and detection of outbreaks of vibriosis infection, has been widely used in many countries. In this study, we developed a molecular assay, named multiplex ligation reaction based on probe melting curve analysis (MLMA), for simultaneous identification of V. parahaemolyticus 57 K-serogroups. Based on the previous genomes of 418 strains including 39 K-serogroups and the 18 K-serogroups sequences from public databases, we obtained 57 K-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The original sequence of homologous tags was fluorescently labelled for the universal two‐dimensional probe. The function of the probe was the same as that of a fluorescent probe in 2D PCR (Lu et al, 2021 ; Zhan et al, 2020 ). It can bind to homologous cTag, leading to production of different Tm in the MCA process.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The original sequence of homologous tags was fluorescently labelled for the universal two‐dimensional probe. The function of the probe was the same as that of a fluorescent probe in 2D PCR (Lu et al, 2021 ; Zhan et al, 2020 ). It can bind to homologous cTag, leading to production of different Tm in the MCA process.…”
Section: Methodsmentioning
confidence: 99%
“…Although some real-time PCR assays have been described (Dos Santos et al, 2020;Rougemont et al, 2004), they cannot distinguish among multiple Plasmodium species in one-pot reactions, mainly due to limited number of fluorescence channels and only can achieve limited detection of one or two Plasmodium species. Plasmodium species detection assays based on isothermal amplification, such as loop-mediated isothermal amplification (LAMP; Hashimoto et al, 2018;Nolasco et al, 2021;Piera et al, 2017;Tambo et al, 2018), recombinase polymerase amplification (RPA; Lai et al, 2018;Lai & Lau, 2020;Lalremruata et al, 2020), showed great convenience for point-ofcare diagnosis, especially for resource-limited settings, but they lack detection throughput and sensitivity in diagnosis, especially for false-positive or false-negative results. The CRISPR-based diagnostic platform (CRISPR-Dx) is a new emerging nucleic acid detection technology used for point-of-care diagnosis, such as Cas12a-mediated Plasmodium detection assay (Lee et al, 2020), showing great sensitivity and specificity.…”
Section: Introductionmentioning
confidence: 99%